Plasma Mitochondrial DNA Level is a Prognostic Marker in Peritoneal Dialysis Patients - Cheuk-Chun Szeto; Ka-Bik Lai; Kai-Ming Chow; Bonnie Ching-Ha Kwan; Phyllis Mei-Shan Cheng; Vickie Wai-Ki Kwong; Agnes Shin-Man Choy; Chi-Bon Leung; Philip Kam-Tao Li (Karger Publishers, 2016)
Background/Aims: Circulating bacterial DNA fragment is related to systemic inflammatory state in peritoneal dialysis (PD) patients. We hypothesize that circulating mitochondrial DNA, which has a similar structure with bacterial DNA, correlates with systemic inflammatory state and predicts cardiovascular event in new PD patients. Methods: We measured plasma mitochondrial DNA level by quantitative polymerase chain reaction (PCR) in 197 new PD patients and 150 patients with chronic kidney disease. PD patients were followed for 24 months for the development of cardiovascular event, hospitalization, and patient survival. Results: There was a stepwise increase in plasma mitochondrial DNA level with worsening renal function. The average plasma mitochondrial DNA level was 18.0 ± 1.2 PCR cycles. Plasma mitochondrial DNA level correlated with serum CRP level (r = -0.538, p Conclusion: Plasma mitochondrial DNA level significantly correlates with systemic inflammatory state, and is a strong predictor of cardiovascular event as well as the need of hospitalization in new PD patients.